Parametric instability of surface waves at the second harmonic of ion cyclotron frequency - Belyaev, M.R.; Girka, V.O.; Lapshin, V.I. (Вопросы атомной науки и техники, 2003)
Parametric instability of surface waves at the second harmonic of ion cyclotron frequency (SWCF) in plasma filled dielectric planar waveguide is examined in a kinetic approximation. SWCF are extraordinary polarized modes propagating across the external steady magnetic field. Simple analytical expressions for the SWCF frequencies, their damping rates due to collisions between plasma particles and interactions between plasma particles and plasma interface, increments of the parametrical instabilities are found. Increments of the SWCF parametric instabilities are slightly dependent on the transverse dimensions of the plasma layer and they strongly decrease with the SWCF wavelength. The obtained results can be used in controlled fusion researches in order to avoid undesirable regime of the plasma periphery heating in fusion devices during.